Emergence delirium in children undergoing botulinum toxin injections for strabismus correction - Rapuleng, Aletta (University of the Witwatersrand, Johannesburg, 2021)
Background Emergence delirium is an unpleasant complication that may occur in children after general anaesthesia. Botulinum toxin injections for strabismus correction is a short procedure with rapid recovery from anaesthesia, a risk factor for emergence delirium. The aim of this study was to describe the occurrence of emergence delirium and the associated risk factors in children undergoing botulinum toxin injections for strabismus correction at Chris Hani Baragwanath Academic Hospital. Methods A cross-sectional research study design was followed using convenience sampling. The study included ASA I and II children aged 2 – 6 years. Data collected consisted of the participants characteristics, the intraoperative course and the child’s anxiety level as evaluated at induction using the modified Yale Preoperative Anxiety Scale (mYPAS). The Paediatric Anaesthesia Emergence Delirium (PAED) score was used to diagnose emergence delirium in the recovery room. All children received a standardised anaesthetic. Results Sixty-one children were included in the study and 31 (50.8%) developed emergence delirium. Thirty-nine (63.9%) participants showed signs of anxiety with a mean (SD) mYPAS of 41.2 (17.9) out of 100. There was a very weak negative correlation between the highest PAED score and the highest mYPAS (r =-0.0287, p=0.8260). There was a moderate negative, statistically significant correlation between the highest PAED score and age (r =-4850, p=0.0001). Younger age (p=0.0001) and male sex (p=0.0002) were found to predispose participants to emergence delirium. The length of stay in the recovery room was longer in those who experienced emergence. Conclusion In this study, a high occurrence of emergence delirium was found following sevoflurane anaesthesia for botulinum toxin injections for strabismus correction, a short procedure with rapid awakening. Younger preschool children were more likely to develop emergence delirium. It was, however, self-limiting and seldom required treatment.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology to the Faculty of Health Sciences, School of Clinical Medicine ,University of the Witwatersrand, Johannesburg 2021
Keywords: Emergence delirium; children; anaesthesia; UCTD; SDG-3: Good health and well-being